Bacillus subtilis CodY Operators Contain Overlapping CodY Binding Sites - Wray, Lewis V. (American Society for Microbiology, 2011)
CodY is a global transcriptional regulator that is activated by branched-chain amino acids. A palindromic 15-bp sequence motif, AATTTTCNGAAAATT, is associated with CodY DNA binding. A gel mobility shift assay was used to examine the effect of pH on the binding of Bacillus subtilis CodY to the hutPp and ureAp(3) promoters. CodY at pH 6.0 has higher affinity for DNA, more enhanced activation by isoleucine, and a lower propensity for nonspecific DNA binding than CodY at pH 8.0. DNase I footprinting was used to identify the CodY-protected regions in the hutPp and ureAp(3) promoters. The CodY-protected sequences for both promoters were found to contain multiple copies of the 15-bp motif with 6-bp overlaps. Mutational analysis of the hutPp regulatory region revealed that two overlapping sequence motifs were required for CodY-mediated regulation. The presence of overlapping sequence motifs in the regulatory regions of many B. subtilis CodY-regulated genes suggests that CodY binds to native operators that contain overlapping binding sites.